PENGARUH PENYIMPANAN DARAH TERHADAP KADAR HEMOGLOBIN PADA KOMPONEN WHOLE BLOOD DARAH DONOR SEBELUM DAN SESUDAH DISIMPAN SELAMA SATU MINGGU DI PMI KOTA MEDAN - Nelma Nelma; Nia Martha Adiratna (Journal of Indonesian Medical Laboratory and Science, 2023)
Blood transfusion is the process of transferring blood from donors to recipients. Before there is a blood demand for transfusion then the blood will be stored in the refrigerator. The longer the blood is stored the more red blood cells are destroyed because the blood is stored for too long will experience a shift curvadisosiasi oxygen towards the left. The purpose of this study was to determine the effect of blood storage on hemoglobin levels on whole blood donor components before and after being stored for one week of Indonesian Red Cross Medan. This research was conducted with descriptive methodology Hematology Analyzer, The sample used for this study was the donor blood of 30 volunteer donors. The results showed that the mean hemoglobin level of blood before storage was 14.2 g/dL and the mean hemoglobin level of blood after being stored for one week was 16,4 g/dL.It is advisable to the laboratory staff to immediately conduct an examination after sampling so that no difference in yield and donor blood should be transfused immediately to the patient. there is a difference in blood tests immediately and stored for one week on hemoglobin levels It is advisable to the next researcher to use a larger number of samples so that the results obtained are more representative.